Enhanced removal of perfluorooctanoic acid (PFOA) from water using ZnO-Ag-ZnAl2O4 composites: Performance and mechanistic insights - Yang, Heejin; Joe, Hye Jeong; Park, Seong Jik; Kim, Seok Ki; Lee, Chang Gu (Journal of Water Process Engineering, 2024)
Perfluorooctanoic acid (PFOA) is a stable and hydrophobic compound that poses potential health risks due to its accumulation within organisms. The present study synthesized the novel adsorbent ZnO-Ag-ZnAl2O4 through direct pyrolysis for efficient PFOA removal. ZnO-Ag-ZnAl2O4 exhibited superior adsorption performance, with an impressive removal rate of 93.1 %, outperforming the ZnAl (9.8 %), ZnAl2O4 (8.5 %), ZnO-ZnAl2O4 (65.9 %), and ZnO-ZnAl2O4 (65.9 %), with detailed adsorption kinetics and isotherm analysis revealing its high adsorption capacity and strong affinity for PFOA. Thermodynamic analysis revealed spontaneous reaction tendencies with a negative Gibbs free energy (−6.669 kJ/mol) and enthalpy (−2.925 kJ/mol) indicating faster rates at lower temperatures. Density functional theory calculations revealed significant adsorption energy (−1.98 eV) for PFOA on Ag, and higher adsorption energy (−0.91 eV) for ZnO-ZnAl2O4 compared to ZnO and ZnAl2O4 alone, particularly when oxygen-deficient sites were present on its surface. Further analysis of the pKa and ionic strength confirmed that electrostatic attraction was the predominant mechanism for PFOA adsorption onto ZnO-Ag-ZnAl2O4. ZnO-Ag-ZnAl2O4 also effectively reduced the levels of E. coli in livestock wastewater. Based on these results, ZnO-Ag-ZnAl2O4 represents a promising and viable option for the removal of PFOA in practical applications.
Keywords: Ag nanoparticle; Density functional theory; Disinfection; Perfluorochemical; Water treatment